Manajemen Reproduksi Untuk Meningkatkan Produktivitas Ternak Sapi di Kecamatan Lingsar Kabupaten Lombok Barat - Sumadiasa, I Wayan Lanus; Lukman HY, Lukman HY; Zaenuri, Lalu Ahmad; Yuliani, Enny; Aminurrahman, Aminurrahman; Abdi, Wahyu Indra (Universitas Mataram, 2025)
The developing paradigm in society states that livestock farming is merely a side business. However, this paradigm has now transformed into a principle that livestock farming is an integral part of agricultural activities, equally important as other farming practices. The farmers’ principle and expectation to produce offspring quickly can be realized through proper, effective, and efficient reproductive management. Consequently, the costs, labor, and time required for management can also be optimized. The purpose of this Community Service Program (PkM) is to provide knowledge and understanding to farmers regarding proper reproductive management to increase livestock (cattle) productivity. The activity was carried out through educational and participatory approaches, namely counseling and discussion. The target audience consisted of members of a livestock farmer group in Karang Bayan Village. The counseling materials covered the selection of prospective dams and sires, mating management, housing and feeding management for pregnant cows, calving, and weaning. The results of the activity showed that the participants gained knowledge and understanding of cattle development principles based on proper reproductive management. This was evident from their high enthusiasm in listening to and accepting the materials, as well as their active participation during the discussion session. They also expressed their hope to apply the counseling results in their livestock farming practices. The evaluation results indicated that there were no obstacles encountered during the implementation of this PkM activity. In conclusion, farmers have gained an understanding of proper reproductive management, recognizing that livestock farming is just as important as any other occupation.